Reimagining citizenship in postwar Europe - Chin, Rachel 1987-; Huneke, Samuel Clowes; Goltz, Anna von der 1978- (Cornell University Press, 2025)
"Reimagining Citizenship in Postwar Europe explores how diverse groups and individuals from across Europe, ranging from policymakers to migrants, displaced persons and sex workers, challenged and debated the meaningof citizenship after 1945."
Keywords: Citizenship / Europe / History / 20th century; Citizenship / Europe / History / 21st century